2017
DOI: 10.1016/j.foodchem.2017.02.097
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of phenolic compounds on carbonyl-amine reactions produced by lipid-derived reactive carbonyls

Abstract: The degradation of phenylalanine initiated by 2-pentenal, 2,4-heptadienal, 4-oxo-2-pentenal, 4,5-epoxy-2-heptenal, or 4,5-epoxy-2-decenal in the presence of phenolic compounds was studied to determine the structure-activity relationship of phenolic compounds on the protection of amino compounds against modifications produced by lipid-derived carbonyls. The obtained results showed that flavan-3-ols were the most efficient phenolic compounds followed by single m-diphenols. The effectiveness of these compounds wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 24 publications
1
32
0
Order By: Relevance
“…Previous research has shown that most of these ,-unsaturated aldehydes are trapped by phenolic compounds, also under normal cooking conditions (Zamora, Aguilar, Granvogl, & Hidalgo, 2016), and this has been suggested to constitute a protective mechanism of phenolic compounds against the toxicity of these lipid oxidation products . Thus, for example, 2-alkenals suffer the addition of phenolic compounds to produce 2H-chromenols, chromandiols, chromanols, and dihydropyrano[3,2-g]chromenes , and 4,5-epoxy-2-alkenals are rapidly transformed into 1,3a,4,9b-tetrahydro-2H-furo[2,3-c]chromene-2, 7diols and 3,4,4a,9a-tetrahydro-1H-pyrano[3,4-b]benzofuran-3,7-diols (Hidalgo, Delgado, & Zamora, 2017;. However, the potential ability of phenolic compounds to trap 4-oxo-2-alkenals has not been described so far.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that most of these ,-unsaturated aldehydes are trapped by phenolic compounds, also under normal cooking conditions (Zamora, Aguilar, Granvogl, & Hidalgo, 2016), and this has been suggested to constitute a protective mechanism of phenolic compounds against the toxicity of these lipid oxidation products . Thus, for example, 2-alkenals suffer the addition of phenolic compounds to produce 2H-chromenols, chromandiols, chromanols, and dihydropyrano[3,2-g]chromenes , and 4,5-epoxy-2-alkenals are rapidly transformed into 1,3a,4,9b-tetrahydro-2H-furo[2,3-c]chromene-2, 7diols and 3,4,4a,9a-tetrahydro-1H-pyrano[3,4-b]benzofuran-3,7-diols (Hidalgo, Delgado, & Zamora, 2017;. However, the potential ability of phenolic compounds to trap 4-oxo-2-alkenals has not been described so far.…”
Section: Introductionmentioning
confidence: 99%
“…Epoxyalkenals are minor lipid oxidation products, but they react rapidly with amino acids, aminophospholipids and proteins producing their rapid degradation at the same time that non-enzymatic browning is produced by means of carbonyl-amine reactions (Hidalgo & Zamora, 1993). However, previous studies have pointed out that they are rapidly scavenged in the presence of certain phenolic compounds, which included single m-diphenols and flavan-3-ols (Hidalgo, Delgado, & Zamora, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…As model phenolic compounds, only simple m-diphenols were employed, namely 2methylresorcinol and 2,5-dimethylresorcinol. These phenolic compounds were selected because carbonyl-phenol adducts are formed mainly with phenolic compounds having two hydroxyl groups at metha positions (Salazar, Arámbula-Villa, Hidalgo, & Zamora, 2014), and simple m-diphenols are efficient epoxyalkenal-trapping agents (Hidalgo, Delgado, & Zamora, 2017). Alkadienals, phenolic compounds and all other chemicals employed in this study were purchased from Sigma-Aldrich (St. Louis, MO), Fluka (Buchs, Switzerland), or Merck (Darmstadt, Germany) and were either analytical grade or the highest available grade.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations